Apocalypse never : why environmental alarmism hurts us all - Shellenberger, Michael (Harper, an imprint of HarperCollinsPublishers, 2020)
"Environmental expert Michael Shellenberger unleashes a scientific, fact-based broadside against eco-alarmism and the excesses of the New Left, arguing that climate change isn't a 30-year problem, but a 300-year problem"--